FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DERMATITIS PADA PEDAGANG IKAN DI PASAR TRADISIONAL KOTA KISARAN KABUPATEN ASAHAN - Reni Aprinawaty Sirait; Anita Oktaviana Siregar (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2021)
Occupational illness is a disease that arises as a result of exposure to risk factors derived from work. Occupational diseases become one of the diseases that can be experienced by workers in their work, occupational diseases caused by work attitudes can be influenced by improper activities, such as misplaced when bagging fish by not using personal protective equipment so that the risk of dermatitis disease occurs in fish traders in traditional markets. This study aims to find out the factors associated with contact dermatitis due to the work of fish traders in the traditional market of the city of asahan district range. This research is quantitative research with cross sectional sighs conducted in the traditional market of the city range. The population in this study was all fish traders with a total of 52 workers. Samples taken by a total of 34 fishing workers were taken using purposiv sampling techniques. The instrument used is a questionnaire. The test used in this study is using chi-square test. From the results of statistical calculations, if the value of p ≤ α (0.05) means that the hypothesis in this study is shouted that there is a relationship of work attitude, length of work and working period with the incidence of box dermatitis directly on fish traders in the traditional market of the city in the range of 2020. Based on the results of the above research is recommended for the promotion of health and safety, especially regarding the correct work attitude and the dangers of direct contact dermatitis disease that can be experienced more intensively such as holding cooperation between the health service to conduct counseling and for workers to use personal protective equipment such as rubber gloves used as appropriate.